Role of Family in Early Detection Towards Pregnancy Complication Risk - Sri Wayanti; Kharisma Kusumaningtyas; Ira Rahayu Tiyar Sari (Aloha International Journal of Health Advancement (AIJHA), 2018)
Background: Inconveniences in pregnancy cause patological condition, labor complication and risky puerperial period which threatening mother and infant safety if it’s doesn’t handled properly, then cause mortality and morbidity to the mother. One of prevention effort to reduce number of pregnancy complication is family support or family role in early pregnancy complication detection. Still amount of husband or family who doesn’t provide access to health services and needs of the mother during pregnancy. This study is purposed to explain affect of family role in early detection towards pregnancy complication risk. Methods: This study used cross sectional research design. The sample was 80 pregnant mother and the family, selected using simple random sampling technique. The independent variable was role of family in early detection (ANC assistance, labor planning, early complication detection, fundings, transportation providing) and dependent variable was number of pregnancy complication risk. Insrument used in this study were questionnaire and MCH-book. Data were analyzed using Chi Square test. Result: ANC assistance influenced number of complication with p-value of 0.005, labor planning didn’t influence number of complication with p-value of 0.313, early complication detection influenced complication with p-value of 0.023, funding didn’t influence complication with p-value of 0.864 and transportation didn’t influence complication with p-value of 0.864. Conclusion: Role of husband in ANC assistance and early complication detection ifluence number of pregnancy complication risk, if husband did the role in ANC assistance and early detection well so pregnancy complication would not occurs. Role of husband in labor planning, funding and transportation doesn’t influence number of pregnancy complication risk. Pregnant mothers are expected can involve husband and the family in antenatal care process so pregnancy complication risk could be detected earlier. Earlier detection can help reducing further pregnancy complication. Keywords: role, family (husband), pregnancy complication